Ayat perintah dalam novel Kabus di Perbukitan - Angterian, Siti Mahani; Mohammad, Hasnah; Raja Ariffin, Raja Masittah (Persatuan Linguistik Malaysia, 2014)
This article is related to the imperative sentences in the novel “Kabus di Perbukitan”. This novel is one of the novels selected as a component of Malay literature which is compulsory subject for form five students in several states including Johor. The objectives of this study is to identify the type and frequency of imperative sentences in the novel. This study uses textual analysis methods. The theory used is Generative Transformation. This study shows that the imperative sentences are frequently used in the novel are errand, prohibition and demand. The results are expected to improve the understanding and help students’ knowledge to master Malay grammar, especially on the use of imperative sentences and to guide students to be better in Malay language writing.